The abusive use of benzodiazepines due to the Covid-19 pandemic (Research, Society and Development, 2023)
Introduction: The Covid-19 pandemic has had a severe impact on the mental health and well-being of people around the world. While many individuals adapted, others experienced mental health issues, in some cases as a consequence of the illness. General Objective: The present study aimed to carry out a bibliographical review on the abusive use of benzodiazepines due to the Covid-19 Pandemic. Methodology: A systematic literature review was carried out, where the results of the main studies contained in the scientific databases SciELO, LILACS and PubMed in Portuguese were collected. A total of 14 articles that met the objectives and inclusion criteria were selected. A table and three graphs were created with the purpose of objectively presenting the main information collected. Results And Discussion: The analysis of the abusive use of benzodiazepines due to the Covid-19 Pandemic serves as a subsidy for public policies, thus increasingly including the pharmacist and the role of Pharmaceutical Care in this problem. The literature describes treatment with benzodiazepines in anxiety, immediately to reduce symptoms, and the results indicate that the abusive use of these drugs was a common practice during the pandemic period, with an increase in their use. Final Considerations: During the Covid-19 pandemic, there was a significant increase in the use of BZDs for GAD symptoms caused by the atypical moment and economic uncertainties.